Development and psychometric testing of the AASPIRE Adult Autism Healthcare Provider Self-Efficacy Scale. (April 2021) - Nicolaidis, Christina; Schnider, Gavin; Lee, Junghee; Raymaker, Dora M; Kapp, Steven K; Croen, Lisa A; Urbanowicz, Anna; Maslak, Joelle
Our objective was to develop a measure of healthcare providers' self-efficacy in providing healthcare to autistic adults and to better understand their training needs. We used a community-based participatory research approach with academic researchers, autistic adults, supporters, and healthcare providers. We developed a one-page questionnaire which included the new 6-item self-efficacy scale, two items on how challenging and rewarding it is to provide care to autistic adults, and seven items on provider characteristics. We surveyed 143 healthcare providers from eight primary care clinics in Oregon and California, United States. Preliminary psychometric testing found the Academic Autism Spectrum Partnership in Research and Education (AASPIRE) Adult Autism Healthcare Provider Self-Efficacy Scale to have good internal consistency reliability (Cronbach's alpha 0.87) and consist of a single factor. A priori hypothesis testing found correlations in the expected directions. Only a minority of providers reported high confidence in communicating with patients (25%); performing physical exams or procedures (43%); accurately diagnosing and treating other medical issues (40%); helping patients stay calm and comfortable during visits (38%); identifying accommodation needs (14%); and making necessary accommodations (16%). While providers need training across all aspects of care related to autism in adulthood, interventions should pay particular attention to helping providers communicate with patients and identify and make accommodations. Lay abstract: The adult healthcare system is ill-prepared to provide high-quality care to autistic adults. Lack of provider training may contribute to the problem, but there are few previously tested survey instruments to guide provider training efforts. Our objective was to develop and test a measure of healthcare providers' confidence (or "self-efficacy") in providing healthcare to autistic adults and to use it to better understand their training needs. We used a community-based participatory research (CBPR) approach, in partnership with academic researchers, autistic adults, supporters, and healthcare providers, throughout the project. We developed a one-page questionnaire and surveyed 143 primary care providers from eight primary care clinics in Oregon and California, United States. Preliminary testing of the AASPIRE Adult Autism Healthcare Provider Self-Efficacy Scale suggests that the measure is reliable and valid. Using this scale, we found only a minority of providers reported high confidence in communicating with patients (25%); performing physical exams or procedures (43%); accurately diagnosing and treating other medical issues (40%); helping patients stay calm and comfortable during visits (38%); identifying accommodation needs (14%); and making necessary accommodations (16%). While providers need training across all aspects of care related to autism in adulthood, interventions should pay particular attention to helping providers communicate with patients, and identify and make necessary accommodations. Future research is needed to further validate this scale and to understand how to meet providers' training needs most effectively.